Volunteerism in Nursing During Disasters: A Concept Analysis - Bilge Kalanlar (Research and Theory for Nursing Practice, 2026)
Background and Purpose: Understanding the factors that influence nurses’ willingness to volunteer during disasters is essential for fostering their active and sustained involvement in disaster preparedness efforts. The aim of the study is to conduct a concept analysis on nurses’ volunteerism in disaster situations. Methods: Walker and Avant’s concept analysis method was used to examine the concept of volunteering. Literature search was conducted in Web of Science, PubMed, ProQuest, ScienceDirect, and CINAHL (Cumulative Index to Nursing and Allied Health Literature) Ultimate databases until July 2025 without any start date restrictions. Electronic databases were searched using the terms “Volunteer” OR “Volunteering” OR “Voluntarism” OR “Volunteerism” AND (“Disaster” OR “Emergency” OR “mass casualty incidents” OR “natural disaster” OR “humanitarian response”) AND (“Nursing” OR “Nurse” OR “Nurs*”). Results: In the 44 studies analyzed, the main characteristics (social and professional responsibility, adaptability, teamwork, and ethical dimension), antecedents (individual and professional identity, disaster education, motivation and commitment, and incentives), and outcomes (professional and personal development, contribution to disaster health care, and social benefits) of volunteering in nursing during disasters were defined. Conclusions: This concept analysis revealed a preliminary model that includes the basic characteristics, antecedents, and consequences of volunteering in nursing during disasters. The model contributes to understanding the multidimensional nature and dynamic structure of volunteerism. Implication for Nursing Practice: This conceptual analysis defines volunteering in disaster situations as follows: characterized by social and professional responsibility, adaptability, teamwork, and ethical dimension; arising from individual and professional identity, disaster training, motivation and commitment, and incentives; and promoting personal, professional, and social benefits.